2020
DOI: 10.1101/2020.05.08.083618
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiple expression assessments of ACE2 and TMPRSS2 SARS-CoV-2 entry molecules in the urinary tract and their associations with clinical manifestations of COVID-19

Abstract: Background: Since December 2019, the novel coronavirus, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), first spread quickly in Wuhan, China, then globally. From previously published evidence, ACE2 and TMPRSS2, are both pivotal entry molecules that enable cellular infection by SARS-CoV-2. Meanwhile, increased expression of pro-inflammatory cytokines, or a "cytokine storm," is associated with multiple organ dysfunction syndrome that is often observed in critically ill patients. Methods: We investi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 43 publications
(45 reference statements)
1
22
0
Order By: Relevance
“…It is implicit that co-expression of ACE2 and transmembrane protease F I G U R E 1 Possible effects of SARS-CoV-2 on the function of main types of testicular cells by an altered ACE-2 signalling pathway. ACE2: angiotensin-converting enzyme-2; ASA: anti-sperm antibody serine 2 (TMPRSS2) is essential for involvement of a tissue by SARS-CoV-2, and a recent study has shown that the testis has a high coexpression of ACE2 and TMPRSS2 (Ren et al, 2020).…”
Section: Role Of Ace2-angiotensin-(1-7)-mas Receptor Axis In Spermamentioning
confidence: 99%
See 2 more Smart Citations
“…It is implicit that co-expression of ACE2 and transmembrane protease F I G U R E 1 Possible effects of SARS-CoV-2 on the function of main types of testicular cells by an altered ACE-2 signalling pathway. ACE2: angiotensin-converting enzyme-2; ASA: anti-sperm antibody serine 2 (TMPRSS2) is essential for involvement of a tissue by SARS-CoV-2, and a recent study has shown that the testis has a high coexpression of ACE2 and TMPRSS2 (Ren et al, 2020).…”
Section: Role Of Ace2-angiotensin-(1-7)-mas Receptor Axis In Spermamentioning
confidence: 99%
“…A previous study in rodents with autoimmune orchitis showed that an increase in the serum level of IL-6 and its receptor, a cytokine that regulates inflammation and immune response, could be associated with pathogenesis of autoimmune orchitis (Rival et al, 2006). It has been reported that more severe cases of COVID-19 are accompanied by a high level of IL-6, and its receptors are highly expressed in testicular cells (Ren et al, 2020;Shen et al, 2020). This can justify the probable male gonadal involvement and a subsequent possibility of orchitis as a complication of SARS-CoV-2.…”
Section: Role Of Ace2-angiotensin-(1-7)-mas Receptor Axis In Spermamentioning
confidence: 99%
See 1 more Smart Citation
“…High ACE2 and TMPRSS2 expressions have been documented in the respiratory, gastrointestinal, and reproductive system [11,12]. Focusing on the upper respiratory tract, increased ACE2 and TMPRSS2 are found in the respiratory and olfactory mucosa.…”
Section: Anatomical Regions Analyzed In Human Post-mortem Nasal and Omentioning
confidence: 99%
“…Shen et al report similar findings in their pre-print [24]. Another pre-print examining ACE2 expression throughout the urinary tract reported higher expression in testicular gametocytes and in renal proximal tubules [25]. Finally, Wu et al report in their pre-print, the relationship between androgen receptor activation and ACE2 and TMPRSS2 expression, and how this may contribute to the higher mortality from COVID-19 in males [26].…”
Section: Translationalmentioning
confidence: 78%